A tale of two dreams a parable from Mindoro Isang kuwento ng dalawang pangarap isang parabula mula sa Mindoro - Gagatiga, Zarah (Lampara books, 2013)
"Two best friends live on an island. One leaves to seek his good fortune. The other one remains to explore the blessings of the island. Find out in this story what fate each friend finds, and what it takes to fulfill one's dream."